NETWORK PROGRAMMABILITY FOR NETWORK ISSUE USING PARAMIKO LIBRARY - Mutiara, Dwi Ayu; Isnaini, Khairunnisak Nur; Suhartono, Didit (Jurnal Teknik Informatika (Jutif), 2023)
In a company, information technology is needed, especially computer networks, to facilitate data communication. The management of a computer network, of course, requires good administration. The criteria for whether or not a network is good can be seen from the performance, reliability, and security indicators so that it will not cause network issues. Events such as server downs, data loss, lost connections, and undetected computers cause the organization's business performance to be disrupted. This study's purpose is to detect network issues with network programmability technology automatically. Paramiko library supports network automation systems and implements OSPF routing protocol in finding the shortest path to send network packets. This study uses the PPDIOO flow, namely prepare, plan, design, implement, operate, and optimize, because it is considered by the flow of making network detection tools. The results showed that the design and implementation of a small-scale network were successfully built by utilizing network programmability technology and the paramiko library, which helps detect network conditions at any time. This design has a dashboard, provisioning, assurance, and policy features that allow administrators to manage and monitor information on each network device. The network design is fitted with REST-API technology and security through a secure shell (ssh) from the Network Controller that can detect the device's connection conditions and the device's health and update the DNS configuration used. Network Issues that have been seen are devices being down, and the connection being lost. Future research can improve features for network troubleshooting when the connection is lost.